Key Factors in Boosting the Efficiency of Scientific Research Administration - Li, Kaitian; Li, Yuning (International Journal of Global Economics and Management, 2024)
The key factors to improve the efficiency of scientific research management include: clear goal setting and strategic planning to ensure the orderly and efficient scientific research work; optimizing resource allocation, material and financial resources to avoid resource waste; strengthening the construction of scientific research team, improving the quality of scientific researchers, team cohesion and innovation ability; establishing scientific evaluation and incentive mechanism to stimulate the enthusiasm of scientific researchers and promote the output of scientific research results; promoting information and digital management, and using modern technology to improve management efficiency and quality. By comprehensively applying these pivotal factors, the standard of scientific research management can undergo a marked enhancement. This comprehensive approach not only ensures the efficient allocation of resources but also fosters a collaborative and innovative research environment. The optimization of management systems and processes leads to increased efficiency and productivity, while the emphasis on team collaboration and communication fosters a stronger sense of unity and purpose among researchers.